Mysticism and understanding : murmurs of meaning(fulness) - unheard silences of Psalm 1 - Lombaard, Christo (Old Testament essays, 2014)
In this paper, two contributions are made. First, the aspect of faith impulses behind the text of Ps 1 are traced, also as an indication of this aspect being overlooked in recent research reviews on Psalter scholarship. Second, the seeming oversimplification of questions of theodicy in this Psalm is characterised here as not ignorance on the part of its author/s, but as taking a considered stance within a highly complex philosophical-theological debate within postâ??exilic Israel. Such a realisation however requires careful "listening" to the implied religious situation to which the text spoke, an exercise which is methodologically difficult, yet which is historically and theologically important.